A Super Efficient PCP System for Transporting Minerals and Mine Wastes (International Mineral Processing Congress, 2014)
Under the sponsorship of the U.S. Department of Energy, a project was completed in 2005, which studied the use of a special pneumatic capsule pipeline (PCP) system, driven by linear induction motor (LIM), for transporting minerals and/or mine wastes. In this study, the pipeline is a rectangular tube of 1m × 1m cross section. The capsules are similar to railroad cars running on small rails imbedded in the tube. A LIM is placed AT the entrance of the tube to transfer power electro-magnetically from the LIM to capsules. The capsules going through the LIM, propelled by the electromagnetic field generated by the LIM, move faster than the air and hence impart energy into the airflow. This in turn pushes the capsules in the tube forward. When the tube is long (say longer than 10 km), additional LIMs may be needed along the tube to serve as booster pumps. An advantage of using LIMs instead of blowers as used in ordinary PCPs is that capsules can pass through the LIMs unhindered. This enables the use of booster pumps for long tubes. It also enables PCP to achieve much higher cargo throughput than that of PCPs using blowers, thereby reducing unit cost ($ per ton-km). Advantages of using capsules with steel wheels running on steel rails in the tubes including: (1) contact friction is only about one-fifth of that using rubber tires, thereby conserving energy, (2) capsules can run at a much higher speed than those using rubber tires without overheating and damaging the tires, and (3) rails make capsule motion control simple; they restrict lateral movement of capsules, and make branching easy-by using standard rail crossing equipment. This advanced PCP system combines the advantages of LIM with the advantages of rails, resulting in a super-efficient tube system having throughputs an order of magnitude greater than that of conventional PCPs, and having an energy efficiency better than railroad transport. Analysis shows that the system is highly cost-effective when throughput is high-at least 5 million tons per year. The system is most suitable for long-distance transportation of minerals (including coal and flyash) and wastes (including both mine wastes and municipal solid waste).